Peningkatan Kapasitas Guru Biologi Madrasah Aliyah dalam Menyusun Tes Berbasis Higher-Order Thinking Skills (HOTS) Di kabupaten Lombok Tengah - Suhirman Suhirman (Prodi Tadris IPA Biologi UIN Mataram, 2024)
Increasing the Capacity of Madrasah Aliyah Biology Teachers in Developing Higher-Order Thinking Skills (HOTS) Based Tests is carried out to increase the capacity of biology teachers and provide knowledge on aspects related to HOTS and its measurement aspects and train teachers, especially at the Madrasah Aliyah and High School levels. to be skilled at preparing HOTS-based questions. The method for implementing service activities is in the form of a workshop held at State High School (SMAN) 2, Jonggat District, Central Lombok Regency, which was attended by 25 biology teacher participants, who came from 12 State Madrasah Aliyah. The methods and techniques of service carried out in this activity through six (6) stages are: socialization, Focus Group Discussion (FGD, conducting a higher-order thinking skills (HOTS) based test preparation workshop for 25 Madrasah Aliyah biology teachers, Central Lombok Regency, conducting assistance in testing HOTS test questions developed in each madrasah, conducting workshops analyzing the results of testing HOTS test questions and making decisions, evaluating and reflecting on the implementation of workshop activities and mentoring. From the results of observations of workshop participants and documents that have been used to carry out assessments among students, it was identified that they were still measuring students' abilities on the LOTS (low order thinking skill) dimension, namely level C1 (knowing), level C2 (understanding), and level C3 (applying). Besides that, the use of KKO (operational verb) was generally still leaning at a low level.